Preventing stroke in atrial fibrillation patients – clinical utility of oral anticoagulants - Jhawar MB; Flaker G (Journal of Blood Medicine, 2012)
Manish B Jhawar, Greg FlakerUniversity of Missouri, Division of Cardiovascular Medicine, Columbia, Missouri, USAAbstract: Atrial fibrillation is the most common of the cardiac arrhythmias and is associated with high risk of stroke and systemic thromboembolism. Prevention of these complications is therefore a major component of clinical management in patients with this rhythm disorder. The choice of antithrombotic therapy in any given patient depends on his or her risk profile and needs to be carefully balanced against the risk of bleeding. In this review we discuss the pathophysiology of thrombogenesis in atrial fibrillation, risk factors for systemic thromboembolism in atrial fibrillation, patient risk stratification modules both for systemic thromboembolism and the risk of bleeding, current antithrombotic therapy strategies, clinicoepidemiological evidence that led to their evolvement, the challenges that plague them, recent developments in the field and how they could possibly affect our future clinical decision making.Keywords: atrial fibrillation, systemic thromboembolism, thromboembolism, vitamin K antagonists, oral anticoagulants